E-Module Based on Problem-Based Learning to Improve Junior High School Scientific Literacy: A Literature Review - Diyah Nurmayanti; Fitri Muslihatun; Elya Suci Nabila; Fitria Herawadini (Indonesian Publication Center, 2026)
The low level of scientific literacy among junior high school students has emerged as a major challenge in 21st-century science education. One potential solution is the development of problem-based learning (PBL) e-modules that integrate contextual and student-centered approaches. This study aims to examine the effectiveness of PBL-based e-modules in enhancing the scientific literacy of junior high school students using a systematic literature review (SLR) approach. Data were sourced from scientific articles published between 2016 and 2025 using the Publish or Perish software. An initial pool of 30 articles was narrowed down to 10 primary studies based on predefined inclusion criteria. The analysis was conducted using content analysis techniques, supported by data extraction matrices and synthesis tables, to identify patterns in findings, intervention characteristics, and the strength of evidence across the studies. The results indicate that PBL-based e-modules effectively improve students' scientific literacy, particularly their ability to explain scientific phenomena, interpret data, and draw evidence-based conclusions. Furthermore, these modules foster a more active and contextual learning environment. Therefore, PBL-based e-modules hold significant potential as an innovative alternative for improving the quality of science education in junior high schools.